2021
DOI: 10.38165/jk.v12i1.230
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Pengelolaan Sampah Dengan Tingkat Kepadatan Lalat Di Tempat Penampungan Sementara (Tps)

Abstract: Sampah yang mengalami penimbunan dapat dimanfaatkan oleh lalat sebagai sarang dalam proses perkembangbiakan penyakit. Kepadatan lalat di TPS Kecamatan Sumber Kabupaten Cirebon masih tinggi sehingga memerlukan pengelolaan sampah yang baik. Tujuan penelitian ini untuk mengetahui hubungan pengelolaan sampah dengan tingkat kepadatan lalat.Jenis penelitian yaitu kuantitaif dengan desain penelitian cross sectional. Metode pengumpulan data dengan wawancara dan instrumen penelitian menggunakan Fly grill dan dibantu de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…Research results show there is a connection mean sorting waste with density flies, where sorting waste bad risks 1.5 times density fly tall compared with sorting waste good (PR=1.5, 95% CI=1.2-1.8). The study following research in Cirebon Regency found that there is connection mean sorting waste with density flies (Kristanti et al, 2021) . Sorting waste is action important first in handling waste by whole (Yudhistirani et al, 2016) .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research results show there is a connection mean sorting waste with density flies, where sorting waste bad risks 1.5 times density fly tall compared with sorting waste good (PR=1.5, 95% CI=1.2-1.8). The study following research in Cirebon Regency found that there is connection mean sorting waste with density flies (Kristanti et al, 2021) . Sorting waste is action important first in handling waste by whole (Yudhistirani et al, 2016) .…”
Section: Resultsmentioning
confidence: 99%
“…The high volume of waste in TPS illustrates that that TPS is not yet enough to accommodate generated waste population as well as the system handling waste that is sorting, collecting, and transporting is not yet maximum in Bandung City (Rumakat et al, 2020). Hoarding waste in TPS is used vector as a source of food as well as a nest in the process of reproduction (Kristanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…sebagai indikator bahwa area tersebut tidak hygiene (Hestiningsih, 2017). Standar baku mutu kesehatan lingkungan untuk vector dan binatang pembawa penyakit terdiri dari beberapa jenis yaitu kepadatan dan habitat perkembangbiakannya (Kristanti et al, 2021).…”
Section: Gambar 1 Kegiatan Penyuluhanunclassified